254 OPTIMISING COMMUNICATION WITH FAMILIES OF PATIENTS ON ACUTE STROKE AND GERIATRIC MEDICINE WARDS IN A LARGE TERTIARY HOSPITAL. (18th November 2021) - Killeen, E; Doherty, R; Higgins, M; O'Reilly, A; Brewer, L
Abstract: Background: Good communication with patients and families is important for older adults admitted to acute stroke or geriatric medicine wards, particularly with COVID19-related restricted visiting. These patients often have communication difficulties including aphasia, delirium, cognitive or hearing impairment, limiting their own communication with relatives. Using the Plan, Do, Study, Act (PDSA) approach we undertook a quality improvement project to optimise communication with families of patients on above wards in a large tertiary hospital. Methods: PDSA cycle 1: Staff were surveyed to identify satisfaction level with communication and ways to optimise communication. Inpatients on study wards were identified, we recorded demographic and clinical details and prevalence of communication difficulties. We created a designated folder with individual 'communication sheets' in conjunction with ward doctors and the nurse manager. PDSA cycle 2: We performed a rapid interval audit of the communication folder use. 'Outlier' patients were excluded as their teams did not receive education about folder use. Results: PDSA cycle 1: A total of 90 inpatients on three wards were included, mean age 78y (SD ±14.4y), 47% were male. Three-quarters (73%) had a communication difficulty noted, reported by nursing staff. Two patients were intubated and six had stroke-related aphasia. Half of surveyed staff reported communication with families was suboptimal. Most (86%) suggested a centrally-located communication logbook would be helpful. PDSA cycle 2: Over two weeks, communication sheets were reviewed for all included patients. Median frequency of calls to families was 4 days (range 0–14). Most (79%) had the name of the primary contact clearly documented. Many (52%) included no contact number. Only 9% had secondary contact information documented. Conclusion: Communication with families of patients on acute stroke and geriatric medicine wards was suboptimal. Over a short interval this improved with regular phone calls using specific centrally-located communication folders. Further optimisation of their use is needed.